AN ANALYSIS OF TRANSLATION PROCEDURES FOUND ON ROUTINE FORMULAIC expression IN A SERIAL THE ADVENTUR OF TIN-TIN "THE CALCULUS AFFAIR" COMIC BY HERGE - DWIARDHIKA, Tyna Rahim (2010)
This study reports on the analysis of translation procedures found in the routine formulaic expressions in a serial The Adventures of Tintin "the Calculus Affair" comic by Herge. The study employed a qualitative research design. The data were taken from the comic which were identified and classified based on type of routine formulaic expressions (Coulmas, 1981) and then analyzed based on translation procedures (Newmark, 1988). The findings revealed that the formulaic expressions used in the comic were 59 (4,31%) salutation, 17 (1,24%) introduction, 17 (1,24%) thanks, 13 (0,95%) apologies, 40 (2,95%) excuses, 45 (3,28%) compliments, 5 (0,36%) toasts, 306 (22,36%) claiming, 95 (6,94%) passing a turn, 91 (6,65%) soliciting, 61 (4,45%) interrupting, 15 (1,09%) introducing a topic, 81 (5,89%) request repetition, 68 (4,97%) explication, 7 (0,51%) closing a topic conversation, and 448 (32,74%) announcements. After classifying the procedures into each routine formulaic expressions, it was revealed that the translation procedure mostly found in salutation was 29 (49,15%) literal; 5 (29,41%) literal in introduction; 12 (70,58%) in thanks; 3 (23,07%) literal, reduction, and synonymy in apologies; 17 (42,5%) paraphrase in excuses; 17 (37,77%) paraphrase in compliments; 3 (60%) paraphrase in toasts; 122 (39,86%) paraphrase in claiming; 44 (46,31%) paraphrase in passing a turn; 34 (37,36%) paraphrase in soliciting; 15 (24,59%) paraphrase in interrupting; 8 (53,33%) paraphrase in introducing a topic; 33 (40,47%) literal in request repetition; 22 (32,35%) paraphrase in explication; 5 (71,42%) paraphrase in closing a topic conversation, and 101 (29,02%) paraphrase in announcements. Based on the research, a translator should use paraphrase as a procedure that mostly found in almost all the expression in the comic to make TL more imaginative and expressive because he use his own language thus the TL text easily to be understood by the reader. Meanwhile, literal procedure was used in several expressions in order to produce accurate and clear translation.